Efecto de diferentes concentraciones de potasio en parámetros de calidad en jitomate hidropónico - Ramírez Santoyo, Luis Felipe; Muro Erreguerena, Julio; Díaz Serrano, Fidel René (Acta Universitaria, 2011)
The primary objective of this study was to improve the quality of tomatoes by the manipulation of ionic relations in the nutritive solution based on the hypothesis that potassium influences carotenoid syntheses in tomato fruits. Two experiments were done using a ‘Gabriela’ tomato hybrid in a hydroponic culture system within an intermediate technology greenhouse. A standard solution (SS) was applied in the vegetative stage, and different solutions with different potassium concentrations (K) were applied in the reproductive stage (SR1 = 20 % K, SR2 = 40 % K, SR3 = 60 % K and SR4 = 45 % K, where the percentage of potassium is given with respect to total cation percentage). All nutritive solutions had values of 30 mg L-1 for total ionic concentration, 6.5, for pH and approximately 3 dS m-1 for CE. In the first experiment, three treatments (SR1, SR2 and SR3) were each tested eight times, and in the second experiment, two treatments (SR2 and SR4) were each tested sixteen times. Treatment SR4 significantly surpassed SR2 in all the quality parameters for each one of selected clusters (the 1st, 3th, 5th, 7th and 9th) except in β-carotene and pH. Potassium significantly affects the concentration of nutraceuticals such as lycopene and β-carotene, which can both be used as inner tomato quality indicators based on analytical and sensorial properties.